Geographic inequalities in infant mortality in Costa Rica, 2008-2012 - Chamizo García, Horacio Alejandro; Behm Ammazzini, Ingrid (Población y Salud en Mesoamérica, 2014)
It is an exploratory ecological study on infant mortality in Costa Rica, its geographical inequities and social determinants. The infant mortality rate, the relative risk of die on children under one year by territorial unit are calculated (since 2008 to 2012) and represented cartographically. The spatial pattern of infant mortality was analyzed and its correlations with socio-economical index like the human development index, gini and a synthetic indicator of environmental quality at household and community levels. The areas with the highest risk of death are found to border and coastal areas as well as lower socioeconomic status and environmental quality. To the extent that the socio-economic and environmental conditions in the cantons are worst tends to increase the risk of infant mortality.